Relationship between Risk Factors and Hypertension in Working Area of Oesapa Public Health Center Kupang City - Linda Aryanti Mahoklory; Apris A. Adu; Deviarbi Sakke Tira (Lontar : Journal of Community Health, 2023)
Hypertension is a silent disease or killer that occurs without causing symptoms and complaints. 2018 Basic health research reported that the prevalence of hypertension in Indonesian aged 18 years increased from 2013 to 2018. This study aimed to analyze the relationship between risk factors and hypertension in the working area of Oesapa public health center Kupang city in 2020. The method of this study is analytical observation with a case-control study design. The sampling technique used was simple random sampling which consists of 49 sample cases and 49 controls. Data analysis used a chi-square statistical test, and the strength of the relationship between risk factors was calculated by odds ratio (OR) value. The results showed that the risk factors associated with the incidence of hypertension in the working area of Oesapa public health center Kupang city in 2020 were age 18 (p= 0.04; OR= 4.5), smoking habits (p= 0.035; OR= 2.728), lack of activity physical (p= 0.001; OR= 4.471), stress (p= 0.025; OR= 2.750) and consumption of NaCl (p= 0.026; OR= 2.719). While the risk factors that were not associated with the incidence of hypertension in the working area of Oesapa public health center Kupang city in 2020 were gender (p= 0.685; OR= 1.280) and alcohol consumption habits (p= 0.355; OR =2.195). The community is suggested to prevent hypertension risk and improve their health status by conducting regular blood pressure checks at health services.